2006
DOI: 10.1152/jn.00512.2006
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Evoked Potentials Are Graded and Somatotopically Organized Anteroposteriorly in the Operculoinsular Cortex of Anesthetized Monkeys

Abstract: Baumgärtner, Ulf, Wiebke Tiede, Rolf-Detlef Treede, and A. D. (Bud) Craig. Laser-evoked potentials are graded and somatotopically organized anteroposteriorly in the operculoinsular cortex of anesthetized monkeys. J Neurophysiol 96: [2802][2803][2804][2805][2806][2807][2808] 2006. First published August 9, 2006; doi:10.1152/jn.00512.2006. The operculoinsular cortical region has a major role in the representation of noxious stimuli, based on functional imaging observations, clinical lesion studies, and EEG recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…Since the physical characteristics of perceived and unperceived nociceptive stimuli were matched, our finding suggests that the magnitude of the N1 wave is mainly driven by the magnitude of the eliciting nociceptive input, rather than by the magnitude of pain perception. Consistent with this view, Baumgärtner et al (2006) showed that the N1 wave can be recorded in anesthetized monkeys. Therefore, our results suggest that the correlation between the magnitude of the N1 wave and pain perception that was reported in two of our recent studies did not result from a relationship between the N1 wave and pain perception per se, but instead, was mostly determined by explicit or unavoidable (Iannetti et al, 2005) variations in the strength of the peripheral nociceptive input.…”
Section: Discussionsupporting
confidence: 53%
“…Since the physical characteristics of perceived and unperceived nociceptive stimuli were matched, our finding suggests that the magnitude of the N1 wave is mainly driven by the magnitude of the eliciting nociceptive input, rather than by the magnitude of pain perception. Consistent with this view, Baumgärtner et al (2006) showed that the N1 wave can be recorded in anesthetized monkeys. Therefore, our results suggest that the correlation between the magnitude of the N1 wave and pain perception that was reported in two of our recent studies did not result from a relationship between the N1 wave and pain perception per se, but instead, was mostly determined by explicit or unavoidable (Iannetti et al, 2005) variations in the strength of the peripheral nociceptive input.…”
Section: Discussionsupporting
confidence: 53%
“…Until now, localization of these functions was only performed by considering an anteroposterior subdivision. This ignored the gyral and sulcal architecture and failed to separate the opercular region from the insula itself [56,57] . Given the diversity of insular functions, it would be interesting to consider their location with respect to the gyral and sulcal anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, nociception is not synonymous with pain, which is experienced as a conscious percept. Indeed, nociception can trigger brain responses without necessarily causing the feeling of pain [2][3][4]. On the other hand, pain can occur in the absence of nociceptive input [5].…”
Section: Introductionmentioning
confidence: 99%